2021
DOI: 10.21203/rs.3.rs-183642/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An Adult Plant Stripe Rust Resistance Gene Maps on Chromosome 7A of Australian Wheat Cultivar Axe

Abstract: Australian wheat cultivar Axe produced resistant to moderately resistant stripe rust responses under field conditions and was exhibiting seedling response varying from 33C to 3+ under greenhouse conditions. Experiments covering tests at different growth stages (2nd, 3rd and 4th leaf stages) demonstrated the clear expression of resistance at the 4th leaf stage under controlled-environment greenhouse conditions. A recombinant inbred line (RIL) population was developed from the Axe/Nyabing-3 (Nyb) cross. Genetic … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Certain APR genes/ QTL, such as Yr18, Yr29 and Yr46 (Rosewarne et al, 2013) and QYrst.wgp-6BS.1/Yr78 (Santra et al, 2008;Dong et al, 2017), have been demonstrated to confer durable resistance sensu Johnson (1984) and Line (2002). There are also reports where APR was detectable as early as at the 4th leaf stage (Ma and Singh, 1996;Quan et al, 2013;Segovia et al, 2014;Chhetri et al, 2016;Kanwal et al, 2021), being described as "mid-stage resistance" (Kanwal et al, 2021) and "juvenile stage" resistance (Segovia et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Certain APR genes/ QTL, such as Yr18, Yr29 and Yr46 (Rosewarne et al, 2013) and QYrst.wgp-6BS.1/Yr78 (Santra et al, 2008;Dong et al, 2017), have been demonstrated to confer durable resistance sensu Johnson (1984) and Line (2002). There are also reports where APR was detectable as early as at the 4th leaf stage (Ma and Singh, 1996;Quan et al, 2013;Segovia et al, 2014;Chhetri et al, 2016;Kanwal et al, 2021), being described as "mid-stage resistance" (Kanwal et al, 2021) and "juvenile stage" resistance (Segovia et al, 2014).…”
Section: Introductionmentioning
confidence: 99%